Non‐invasive home ventilation using the average volume assured pressure support feature in an infant with severe bronchopulmonary dysplasia and chronic respiratory failure - Vishal Saddi; Ganesh Thambipillay; Arthur Teng (Wiley, 2020)
Abstract Introduction While majority of infants with bronchopulmonary dysplasia (BPD) can be discharged home without low flow oxygen or on supplemental low flow oxygen, some require long term home mechanical ventilation. Case presentation We present a case of an extremely premature infant with severe bronchopulmonary dysplasia who was successfully managed at home on a new feature of non‐invasive ventilation called average volume assured pressure support (AVAPS) without the need for tracheostomy. The AVAPS feature enables the machine to deliver a consistent tidal volume by automatically adjusting the inspiratory pressure within a set range. Conclusion The use of AVAPS feature in our case improved ventilation as indicated by a more stable gas exchange profile, making home non‐invasive ventilation a more practicable method of managing severe BPD in this infant.